Exercise training improves adipose tissue metabolism and vasculature regardless of baseline glucose tolerance and sex - Sanna Maria Honkala; Piryanka Motiani; Riikka Kivelä; Karthik Amudhala Hemanthakumar; Erik Tolvanen; Kumail Kumar Motiani; Jari-Joonas Eskelinen; Kirsi A Virtanen; Jukka Kemppainen; Marja Anneli Heiskanen; Eliisa Löyttyniemi; Pirjo Nuutila; et al. (BMJ PUBLISHING GROUP, 2022)
Introduction We investigated the effects of a supervised progressive sprint interval training (SIT) and moderate-intensity continuous training (MICT) on adipocyte morphology and adipose tissue metabolism and function; we also tested whether the responses were similar regardless of baseline glucose tolerance and sex.
Research design and methods 26 insulin-resistant (IR) and 28 healthy participants were randomized into 2-week-long SIT (4-6x30 s at maximum effort) and MICT (40-60 min at 60% of maximal aerobic capacity (VO2peak)). Insulin-stimulated glucose uptake and fasting-free fatty acid uptake in visceral adipose tissue (VAT), abdominal and femoral subcutaneous adipose tissues (SATs) were quantified with positron emission tomography. Abdominal SAT biopsies were collected to determine adipocyte morphology, gene expression markers of lipolysis, glucose and lipid metabolism and inflammation.
Results Training increased glucose uptake in VAT (p<0.001) and femoral SAT (p<0.001) and decreased fatty acid uptake in VAT (p=0.01) irrespective of baseline glucose tolerance and sex. In IR participants, training increased adipose tissue vasculature and decreased CD36 and ANGPTL4 gene expression in abdominal SAT. SIT was superior in increasing VO2peak and VAT glucose uptake in the IR group, whereas MICT reduced VAT fatty acid uptake more than SIT.
Conclusions Short-term training improves adipose tissue metabolism both in healthy and IR participants independently of the sex. Adipose tissue angiogenesis and gene expression was only significantly affected in IR participants.